STRATEGI GURU DALAM MENGEMBANGKAN KECERDASAN SPIRITUAL ANAK USIA DINI - Imelza, Friska; Amelia, Lina (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
Early Childhood Education (PAUD) is essential in shaping children's character and spiritual intelligence from an early age. This study describes teacher strategies and inhibiting and supporting factors in developing students' spiritual intelligence at TK Negeri 2 Banda Aceh City. The research approach uses a qualitative case study research type. Sampling as research subjects uses a purposive sample of class B teachers as sources and students as observersÃ¢â‚¬â€data collection through observation with subjects, interviews with teachers and documentation during the study. The data results were analyzed using Miles and Huberman with data reduction (codification), data presentation, and conclusion. The results show that the main strategies for developing spiritual intelligence are storytelling and praying together, singing Islamic songs, moral stories, muraja'ah, and educational tours to the mosque. The main supporting factors come from the family environment, social environment, such as school, teachers, and learning media. Meanwhile, inhibiting factors include differences in family backgrounds, limited learning media, and the character of easily distracted children. Efforts to overcome obstacles are carried out through collaboration with parents, spontaneous strategies from teachers through questions and answers, and singing. This research contributes to strengthening the practice of early childhood spiritual education in the context of Islamic education and is a reference in developing character learning strategies in PAUD environments.